Frequent human‐poultry interactions and low prevalence of Salmonella in backyard chicken flocks in Massachusetts. (16th November 2018) - McDonagh, Alyssa; Leibler, Jessica H.; Mukherjee, Jean; Thachil, Anil; Goodman, Laura B.; Riekofski, Cassidy; Nee, Amanda; Smyth, Khrysti; Forrester, Janet; Rosenbaum, Marieke H.
Abstract: The backyard chicken (BYC) movement in the USA has increased human contact with poultry and subsequently, human contact with the pathogen Salmonella . However, to date, there have been few studies assessing prevalence of Salmonella in backyard flocks, despite the known public health risk this zoonotic bacterium poses. The objective of this study was to characterize human‐BYC interactions and assess the prevalence of Salmonella among BYC flocks. We interviewed 50 BYC owners using a structured questionnaire to determine flock and household characteristics that facilitate contact with BYC and that may be associated with Salmonella in the BYC environment. Composite faecal material, cloacal swabs and dust samples from 53 flocks housed on 50 residential properties in the Greater Boston, Massachusetts area were tested for Salmonella using standard culture techniques and confirmed using Matrix‐Assisted Laser Desorption/Ionization‐Time of Flight Mass Spectrometer. Microbroth dilution and whole genome sequencing were used to determine phenotypic and genotypic resistance profiles, respectively, and sequence results were used to determine multilocus sequencing type. No owners self‐reported a diagnosis of salmonellosis in the household. Over 75% of a subset of owners reported that they and their children consider BYC pets. This perception is evident in how owners reported interacting with their birds. Salmonella enterica subspecies enterica serotype Kentucky ST152 (serogroup C)—a strain not commonly associated with human infection—was confirmed in one flock, or 2% of tested flocks, and demonstrated resistance to tetracycline and streptomycin. We detected Salmonella at low prevalence in BYC. Further study of the health effects of exposure to zoonotic gastrointestinal pathogens such as Salmonella among families with BYC is warranted.